A HYDROLOGICAL MODELLING APPROACH IN IDENTIFYING RAINWATER POTENTIAL FOR LONG-TERM WATER AND FOOD RESOURCE MANAGEMENT IN SEVERE CLIMATIC SCENARIOS: A CASE STUDY OF SOUTHERN KADUNA (FUDMA JOURNAL OF SCIENCES, 2023)
The unavailability of freshwater in the Sahel region of Africa is one of the hindrances to meeting sustainable development goals. This, coupled with an increasing population, makes irrigation demand unmet. The SWAT hydrological model was used alongside the Water Evaluation and Planning Tool (WEAP) to analyse the current and future conditions under different climatic scenarios. The study found the impact due to urban expansion and climatic change to be severe in the irrigation sector, with an unmet demand of 258 Mm3. The unmet total future demand due to climate variation between 2006 to 2030 is observed to be 30 Mm3,273Mm3,370Mm3,368Mm3 for the climatic scenarios as considered in the study. The SWAT hydrological model produced a Nash-Sutcliffe of 0.837 and 0.75 during calibration and validation, respectively. studies considering water quality  are recommended for future studies with also an evaluation of the sustainability of aquatic organisms within the catchment.
Keywords: Food management; water resource management; Hydrological Modelling; Unmet Demand